MEDIATION AS AN ALTERNATIVE FOR RESOLVING INDIVIDUAL LABOR DISPUTES IN UKRAINE: ESSENCE, PRINCIPLES, ADVANTAGES - Гринь, Д. В. (Київський національний університет імені Тараса Шевченка, 2021)
The work examines the essence of mediation as an alternative way to resolve individual labor disputes, as well as examines its advantages and principles, which are the basis of this out-of-court dispute resolution procedure. It was concluded that mediation is currently a more accessible option for resolving disputes for the citizens of our country, which has its own universal constructive character. This is a special form of negotiation, its nature is determined by the place and role of the mediator in this procedure. It has the following features: it is a special type of negotiation that has a certain structure; mandatory participation of a mediator who is not a representative of any of the parties; the mediator assists the parties in conducting negotiations and reaching a mutually acceptable solution, at the same time does not examine the evidence and does not establish the facts, and also does not force the parties to make a certain decision and does not give advice on possible decision options, and does not make a binding decision for the parties; the active role of the parties themselves in the negotiations regarding the independent search for possible solutions. The advantages of mediation include: saving time and financial resources; the ability to influence the result; confidentiality of the procedure and less stress; the possibility of maintaining or restoring business relations; the possibility of preventing conflicts in the future; in the case of successful mediation - a guarantee of execution of the decision. The main advantage of resolving disputes through mediation is that the parties to the conflict fully control the decision-making process for settling the dispute, and the final resolution of the conflict depends on the parties, not on the court. The principles of mediation as a pre-trial way of resolving labor disputes and protecting the labor rights of employees should be understood as the original, fundamental, inviolable principles, ideas that underlie the introduction and further implementation of the relevant procedure. The main ones, according to the legislation on mediation, include the principle of voluntariness, confidentiality, neutrality, independence and impartiality of the mediator, self-determination and equal rights of the mediation parties.

У роботі досліджено сутність медіації як альтернативного способу вирішення індивідуальних трудових спорів, а також розглянуто її переваги та принципи, які покладено в основу цієї позасудової процедури вирішення спорів. Зроблено висновок, що медіація на сьогодні є більш доступним варіантом вирішення спорів для громадян нашої держави, яка має свій універсальний конструктивний характер. Це особлива форма переговорів, її природа визначена місцем і роллю медіатора в цій процедурі. Їй притаманні такі риси: це особливий вид переговорів, що має певну структуру; обов’язкова участь медіатора, який не є представником жодної зі сторін; медіатор сприяє сторонам у проведенні переговорів і досягненні взаємоприйнятного рішення, водночас не досліджує докази і не встановлює факти, а також не примушує сторони до прийняття певного рішення та не надає поради щодо можливих варіантів рішень, і не виносить обов’язкового для сторін рішення; активна роль самих сторін у переговорах щодо самостійного пошуку можливих рішень. До переваг медіації слід віднести: економія часу та фінансових ресурсів; можливість впливати на результат; конфіденційність процедури та менший стрес; можливість збереження чи відновлення ділових взаємин; можливість запобігти виникненню конфліктів у майбутньому; у разі успішної медіації – гарантія виконання рішення. Основною ж з переваг вирішення спорів через медіацію є те, що сторони конфлікту повністю контролюють процес прийняття рішення із врегулювання спору й остаточне розв’язання конфліктного питання залежить саме від сторін, а не від суду. Під принципами медіації як досудового способу вирішення трудових спорів і захисту трудових прав працівників слід розуміти вихідні, основоположні, непорушні засади, ідеї, які лежать в основі запровадження та подальшого здійснення відповідної процедури. До основних з них  відповідно до законодавства про медіацію відносяться принцип добровільності, конфіденційності, нейтральності, незалежності та неупередженості медіатора, самовизначення та рівності прав сторін медіації.
МЕДІАЦІЯ ЯК АЛЬТЕРНАТИВА ВИРІШЕННЯ ІНДИВІДУАЛЬНИХ ТРУДОВИХ СПОРІВ В УКРАЇНІ: СУТНІСТЬ, ЗАСАДИ, ПЕРЕВАГИ
Keywords: employee; employer; protection; labor rights; labor disputes; mediation; mediator; principles.; працівник; роботодавець; захист; трудові права; трудові спори; медіація; медіатор; принципи.